Significant association of rare variant p.Gly8Ser in cardiac sodium channel β4‐subunit SCN4B with atrial fibrillation. (1st March 2019) - Xiong, Hongbo; Yang, Qin; Zhang, Xiaoping; Wang, Pengxia; Chen, Feifei; Liu, Ying; Wang, Pengyun; Zhao, Yuanyuan; Li, Sisi; Huang, Yufeng; Chen, Shanshan; Wang, Xiaojing; et al.
Abstract: Atrial fibrillation (AF) affects 33.5 million individuals worldwide. It accounts for 15% of strokes and increases risk of heart failure and sudden death. The voltage‐gated cardiac sodium channel complex is responsible for the generation and conduction of the cardiac action potential, and composed of the main pore‐forming α‐subunit Nav 1.5 (encoded by the SCN5A gene) and one or more auxiliary β‐subunits, including Nav β1 to Nav β4 encoded by SCN1B to SCN4B, respectively. We and others identified loss‐of‐function mutations in SCN1B and SCN2B and dominant‐negative mutations in SCN3B in patients with AF. Three missense variants in SCN4B were identified in sporadic AF patients and small nuclear families; however, the association between SCN4B variants and AF remains to be further defined. In this study, we performed mutational analysis in SCN4B using a panel of 477 AF patients, and identified one nonsynonymous genomic variant p.Gly8Ser in four patients. To assess the association between the p.Gly8Ser variant and AF, we carried out case‐control association studies with two independent populations (944 AF patients vs. 9, 81 non‐AF controls in the first discovery population and 732 cases and 1, 291 controls in the second replication population). Significant association was identified in the two independent populations and in the combined population ( p  = 4.16 × 10 −4, odds ratio [OR] = 3.14) between p.Gly8Ser and common AF as well as lone AF ( p  = 0.018, OR = 2.85). These data suggest that rare variant p.Gly8Ser of SCN4B confers a significant risk of AF, and SCN4B is a candidate susceptibility gene for AF.